Taking care of the population in vulnerable situation: performance and challenges faced by a team of the office on the street in a city of the interior of Maranhão (Research, Society and Development, 2021)
Objective: to understand how the office team works on the street and what challenges are faced in maintaining the health of the homeless population. Method: qualitative exploratory and descriptive study, carried out with team professionals, through interviews, in June 2021. Results: The team works by providing assistance in accordance with the basic principles of the Unified Health System (SUS) and the National Policy for the Homeless Population. Also through means that collaborate in care, including harm reduction as a strategy, there is an active listening action with the reception and articulation of the network. Final considerations: Through the study, it was found that the team professionals have knowledge about the performance and purpose of the office on the street, demonstrating the importance of this team for the population in a vulnerable situation. It was also observed the articulations with the health network to provide continued care with the objective of reducing damage.